The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ejbt.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a eukaryotic expression vector for pEGFP-FST and its biological activity in duck myoblasts

Abstract: Background: Follistatin (FST), a secreted glycoprotein, is intrinsically linked to muscle hypertrophy. To explore the function of duck FST in myoblast proliferation and differentiation, the pEGFP-FST eukaryotic expression vector was constructed and identified. The biological activities of this vector were analyzed by transfecting pEGFP-FST into cultured duck myoblasts using Lipofectamine™ 2000 and subsequently determining the mRNA expression profiles of FST and myostatin (MSTN). Results: The duck pEGFP-FST vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The BrdU assay was employed to analyse the proliferation states of the myoblasts, and the results showed that the percentage of BrdU-labelled nuclei was higher in the pEGFP-duFST group ( Figures 1 D– 1 E, P <0.05), indicating a positive role of FST on duck myoblast proliferation. In transient transfection assay, our previous research showed that pEGFP-N1 alone did not have significant effects on the myoblast proliferation, the myoblast vitality and the mRNA expression of FST [ 20 ]. Thus, we can exclude the potential influences of EGFP on the endpoint analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The BrdU assay was employed to analyse the proliferation states of the myoblasts, and the results showed that the percentage of BrdU-labelled nuclei was higher in the pEGFP-duFST group ( Figures 1 D– 1 E, P <0.05), indicating a positive role of FST on duck myoblast proliferation. In transient transfection assay, our previous research showed that pEGFP-N1 alone did not have significant effects on the myoblast proliferation, the myoblast vitality and the mRNA expression of FST [ 20 ]. Thus, we can exclude the potential influences of EGFP on the endpoint analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Among the core genes that regulate muscle development, mstn is the most important negative regulator (Parsons et al 2006 ). Generally, mstn keeps muscle cells in G0/G1 and G2 phases by regulating the binding of Myog and Smad proteins, thereby restricting the differentiation and proliferation of myoblasts (Li et al 2014 ). Previous studies have shown that the regulation of mstn is a very complex process.…”
Section: Discussionmentioning
confidence: 99%
“…Among the core genes that regulate muscle development, mstn is the most important negative regulator (Parsons et al 2006). Generally, mstn keeps muscle cells in G0/G1 and G2 phases by regulating the binding of Myog and Smad proteins, thereby restricting the differentiation and proliferation of myoblasts (Li et al 2014). Previous studies have shown that the regulation of mstn is a very complex process.…”
Section: Molecular Mechanism Which Mstn Affects and Lipid Metabolismmentioning
confidence: 99%